Traumatic Diaphragmatic Rupture with Visceral Herniation: A Case Report - Kusuma, Widia Trilaksana; Sindhu, Wayan; Prasista, Yudha (Jurnal Ilmu Kesehatan dan Kesehatan, 2023)
Background: The diaphragm is a dome-shaped respiratory muscle located near the lower ribs, the exact location is below the chest. Diaphragmatic rupture is a medical condition caused by blunt or penetrating trauma, which often leads to herniation of the abdominal viscera into the thoracic cavity. Case: We presented a case in which a 39-year-old man complained of left chest pain and abdominal pain radiated to his back, after involed in a traffic accident. On physical examination, the left chest was left behind when breathing, a dull sound was found on percussion, with diffuse abdominal tenderness. Thoraco Abdomen CT-scan was performed and it concluded that there was a rupture of the left posterior diaphragm with a diameter of 15 cm which caused herniation of the gastric and intestines to the left of thoracic cavity, accompanied by a collapse of the left lung due to blunt trauma. The patient underwent an explore laparotomy with the aim of repairing his diaphragmatic rupture, and splenectomy procedure to remove the affected spleen. Conclusion: Surgery is a mandatory action in order to repair the diaphragm. The choice of the approach to be used, either laparotomy or thoracotomy depends on other organ abnormalities, acute or latent cases, stable or unstable condition of the patient and also depends on the experience of the operator.